Cervical cancer in pregnancy: diagnosis, staging and treatment. (20th December 2021) - Howe, Tamara; Lankester, Kate; Kelly, Tony; Watkins, Ryan; Kaushik, Sonali
Abstract : Key Content: Cervical cancer is the commonest gynaecological malignancy diagnosed in pregnancy. Cancer symptoms may mimic complications of pregnancy, thus delaying diagnosis. Staging of cervical cancer in pregnancy is essential to determine an individual management plan. Treatment of cervical cancer in pregnancy is complex and depends on the stage of cancer and the gestation of the pregnancy. Involvement of a multidisciplinary team is essential in the care of a woman with cervical cancer in pregnancy. Learning Objectives: To understand how to diagnose, stage and treat cervical cancer in pregnancy. To know the risks to the fetus in each trimester, with regard to the various surgical and chemotherapeutic options available to treat cervical cancer in pregnancy. To understand the psychological effects on a woman of a cancer diagnosis in pregnancy. Ethical Issues: How should maternal and fetal risks be balanced while investigating and treating cervical cancer in pregnancy? Consideration of termination of pregnancy to allow timely treatment, alternatively risking delay in treatment and progression of disease.